Nonlinear finite element analysis of damaged and strengthened reinforced concrete beams - Aktas, Muharrem; Sumer, Yusuf (Journal of Civil Engineering and Management, 2014)
Bending test of seven reinforced concrete beams are modeled in finite element program to validate the modeling strategies by comparing the structural response of the beams. Three beams in the set are pre-damaged and strengthened with fiber reinforced composites before the bending tests. Cracks are implemented into the model by inserting geometrical discontinuities to represent the pre-damaged beams. Parametric variables such as crack width, length and interval are chosen to simulate different pre-damage levels. Once the proposed modeling strategies are validated by real experimental tests then 196 finite element models are created to study the effects of pre-damage levels on the moment capacity of reinforced concrete beams repaired with CFRP. Results indicate that inclusion of pre-damage levels by means of cracks into the cross sections have significant effect on beams moment capacity.